Novel NiCo2S4@reduced graphene oxide@carbon nanotube nanocomposites for high performance supercapacitors. Issue 102 (24th October 2016) - Xu, Jingxuan; Yang, Yang; Chu, Hang; Tang, Jianhua; Ge, Yuancai; Shen, Jianfeng; Ye, Mingxin
Abstract : Novel three-dimensional NiCo2 S4 @rGO@CNT nanocomposite electrode material was synthesized. Abstract : We present a simple one-step solvothermal method for in situ growth of nickel cobalt sulfide (NiCo2 S4 ) nanoparticles on the reduced graphene oxide (rGO) sheets and carbon nanotube (CNT) without adding any surfactant. The NiCo2 S4 @rGO@CNT structure was fabricated successfully with the hydrothermal method. When serving as an electrochemical supercapacitor electrode material, the NiCo2 S4 @rGO@CNT delivers a highly improved specific capacitance of 1242.51 F g −1 at the current density of 2.0 A g −1, as compared with that of pure NiCo2 S4 (519.51 F g −1 ) counterpart. Its durability is mainly owing to the synergistic effects of NiCo2 S4, rGO and CNT, further presenting potential applications in energy storage.